Stabilizing the closed SARS-CoV-2 spike trimer - Jarek Juraszek (Nature Portfolio, 2021)
SARS-CoV-2 S protein prematurely refolds to the post-fusion conformation, compromising immunogenic properties and prefusion trimer yield. Here, Juraszek et al. present a stable SARS-CoV-2 S-closed protein variant with increased expression and correct folding, predominantly in closed prefusion conformation.